2011
DOI: 10.1002/bit.23353
|View full text |Cite
|
Sign up to set email alerts
|

Fiber alignment and coculture with fibroblasts improves the differentiated phenotype of murine embryonic stem cell‐derived cardiomyocytes for cardiac tissue engineering

Abstract: Embryonic stem cells (ESCs) are an important source of cardiomyocytes for regenerating injured myocardium. The successful use of ESC-derived cardiomyocytes in cardiac tissue engineering requires an understanding of the important scaffold properties and culture conditions to promote cell attachment, differentiation, organization, and contractile function. The goal of this work was to investigate how scaffold architecture and coculture with fibroblasts influences the differentiated phenotype of murine ESC-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 37 publications
(54 reference statements)
4
77
0
Order By: Relevance
“…Although many PU-based materials have been developed for providing vascular grafts, only few PU scaffolds have so far been studied in the context of myocardial tissue engineering [39,40], even though PU is easy to implant into muscle tissue, because it is stiffer than typical hydrogels. An important goal for myocardial tissue engineering must be the fabrication of materials that allow for the synchronization of electrical signals, and thus enhance the contraction of cardiomyocytes in the scaffold material so that a homogeneous total contraction of the engineered patch is guaranteed.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Although many PU-based materials have been developed for providing vascular grafts, only few PU scaffolds have so far been studied in the context of myocardial tissue engineering [39,40], even though PU is easy to implant into muscle tissue, because it is stiffer than typical hydrogels. An important goal for myocardial tissue engineering must be the fabrication of materials that allow for the synchronization of electrical signals, and thus enhance the contraction of cardiomyocytes in the scaffold material so that a homogeneous total contraction of the engineered patch is guaranteed.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In vitro evaluations underpinned the suitability of electrospun membranes for cardiomyocyte guidance and differentiation as well as maintenance of their contractile function [20][21][22]. The fibrous, anisotropic architecture of electrospun scaffolds compared to solid substrates proved superior for cardiomyocyte maturation and, in particular, cell infiltration and multi-layered tissue formation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2008) observed the cardiac fibroblasts promote remodeling of a preformed collagen matrix and aid in the formation of compact cardiac-like tissue [30]. Parrag et al (2011) studied murine embryonic stem cells derived cardiomyocytes (mESCDCs) attached on polyurethane (PU) scaffolds and also showing construct contraction [31]. These PU scaffolds are important for developing engineered myocardial constructs using mESCDCs and also consider human ESCDCs induced pluripotent stem cell-derived cardiomyocytes for clinically relevant cardiac repair.…”
Section: Interaction Of Cardiac Cells and Xylan/pva Nanofibersmentioning
confidence: 97%